Analysis of main influencing factors of energy dissipation and flow diversion effects of rough-strip energy dissipators in curved spillways based on Plackett–Burman design. Issue 2 (19th January 2023) - Zhang, Honghong; Mu, Zhenwei; Fan, Fan; Yao, Li
Abstract: Rough-strip energy dissipators (R-SEDs) at the bottom of spillway bends have energy dissipation and flow diversion effects on bend flow. In this paper, twelve Plackett-Burman tests were conducted. Energy dissipation rate and coefficient of variation of superelevation were used as evaluation indices. Influencing factors (i.e., relative height, height ratio, spacing, angle and thickness of R-SEDs as well as centerline radius, width, angle and bottom slope of the bend) of R-SEDs' energy dissipation and flow diversion effects were analyzed using Minitab 21.1 in combination with the entropy weight method and the TOPSIS method. Relative height of R-SED and bend angle were significant factors affecting energy dissipation effects; height ratio of R-SED and centerline radius of the bend were significant factors affecting flow diversion effects; the coefficient of variation of superelevation had a larger weight (0.549) than the energy dissipation rate (0.451), indicating that R-SEDs' flow diversion effects were larger than their energy dissipation effects; height ratio of R-SED, centerline radius of the bend and bend angle were significant factors affecting overall energy dissipation and flow diversion effects and selected as key factors for further steepest climbing tests and response surface design. HIGHLIGHTS: R-SEDs were proposed for curved spillways, with a simple structure to facilitate construction. The Plackett–Burman design as the experimental method reduced the number of experiments and effectively facilitated the selection of key influencing factors. A new index coefficient of variation of superelevation was established for evaluating flow diversion effects of R-SEDs, with simple calculation for application.